Enhancing CF/PEEK composites by CF decoration with polyimide and loosely-packed CNT arrays. (December 2019) - Hassan, Elwathig A.M.; Ge, Dengteng; Zhu, Shu; Yang, Lili; Zhou, Jianfeng; Yu, Muhuo
Abstract: The weak interfacial bonding due to non-polarity and poor wettability of carbon fiber (CF) between CF and polyetheretherketone (PEEK) presents a challenge in carbon fibers reinforced CF/PEEK composites. In this study, a combined sizing agent of polyimide and loosely-packed network of carbon nanotubes (CNT) is deposited on the surface of CF, which greatly improve mechanical performances of composites by a synergetic effect of two components. The result demonstrates that ILSS, flexural strength and modulus of modified CF/PEEK composites were enhanced by 71%, 63% and 70%, respectively. It is also found that loosely-packed CNT arrays on CF could better improve flexural strength and modulus for CF/PEEK composite than dense CNT networks on carbon fibers, while the opposite happens for thermosetting composites. The benefit of loosely-packed CNT arrays could be attributed to easier penetration of viscous PEEK melt into this structure compared to dense CNT networks.